KEMAMPUAN SISWA KELAS X SMK NEGERI 2 MEDAN MENGIDENTIFIKASI FAKTA DAN OPINI DALAM SURAT KABAR TRIBUN MEDAN - Br. Perangin-angin, Damentaria; Harahap, Rosmawati (Universitas Islam Sumatera Utara, 2022)
This study aims to describe students' ability to identify factual texts in the Medan Tribune newspaper published in May 9, 11, 13, 22 2022 with the theme of Honda or two-wheeled vehicles. This type of research is quantitative research with descriptive method. This research is said to be quantitative because the data taken will be changed in the form of numbers, namely student scores in determining or distinguishing facts and opinions in the Medan Tribune newspaper. The number of samples taken by the researchers were 36 students from class X TP1. In this study, the instrument used was a written test, namely an essay test to determine facts and opinions. The data found and collected were then analyzed using quantitative descriptive statistical techniques with percentages. The percentage obtained then refers to the criteria for student learning completeness which are determined individually and classically. Students are said to have completed individual learning if students get a score or achieve a minimum ability of 75%, while complete classical learning if the number of students who individually get a percentage of 75% reaches 80% or more of the total sample. The ability to identify facts and opinions from the Medan Tribune newspaper by class X students of SMK Negeri 2 Medan is categorized as classically capable. It is said to be able because the number of students who achieved individual ability 75% reached 80.55% and did not reach the classical completeness criteria, namely 19.44% because they were capable of 75%.